The tourism as a development investment in less developed regions: network behaviour of different cities - Hale Ciraci; Kenan Gocer; Ebru Kerimoglu (European Regional Science Association (ERSA), 2004)
Tourism industry has been used to create new employment opportunities by increasing the business capacity and to provide economic growth in Turkey. But most of the tourism investments have been located in relatively more developed western and southern regions, which are ecologically sensitive coastal areas. It is known that there are important disparities between socio-economic development levels of different regions and tourism industry can be a planning investment in revitalizing the less developed areas. Turkey is a very large country, it has very much climatic regions and natural resources and as it is a place of meeting of many cultures and religions throughout the history, it owns a very rich cultural and archaeological inheritance. In this framework, it is possible to make tourism investments in such fields as urban tourism, sea-sun tourism, winter tourism or religion based tourism. The urban tourism that is able to attract tourists in any season has a very widespread potential in the country and provides us with substantial opportunities for the provinces with only one tourism option such as winter tourism. From 1980s so far, there has been discrete developments thanks to efforts of local governments, the association of tourism investors and the Ministry of Tourism. The Law for Tourism Encouragement enforced in 1982 defined the terms `tourism region', `tourism area' or `tourism center' and provided such concepts with a legal definition and determined the systems of encouragement and means of application in these fields. In establishing these regions, areas and centers, the country has been taken as a whole with its natural, historical, archaeological, socio-cultural and tourism values as well as winter, hunting and water sports, health tourism and religion based tourism potential. But a means to create network by combining different types of tourism and creating a synergy in tourism sector by means of cooperation between the cities has not been followed so far. Combining these different types of tourism and providing cooperation between cities will create a synergy in tourism sector in less developed areas. This study tries to answer the question of which cities can be grouped as a network to cooperate based on tourism industry regarding their tourism potential. In this study using cluster analysis and factor analysis cities are grouped according to their socio-economic development levels. The results of cluster analysis indicate that western-southern, middle-northern, and eastern-southern regions are three major development levels. According to the factor analysis, the provinces grouped in 4 different levels of development in relation to different factors. These spatial settings in Turkey's geography show as to which regions would respond the investments to be made in a shorter period. As the country is very large, the attractive points with a high tourism potential, other than those in the developed regions should be determined and a synergy between the settlement zones should be established in an effort to increase the productivity. It would be possible to coordinate the infrastructure investments to take place in the cities and to define the short, medium and long-term investments with this study.
Keywords: 330